2018
DOI: 10.1111/add.14135
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of smoking cessation during pregnancy: a systematic review and meta‐analysis

Abstract: A wide range of socio-demographics, relationship, social, smoking-related, pregnancy-related, health and psychological factors have been found to predict smoking cessation in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
122
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 91 publications
(318 reference statements)
15
122
6
2
Order By: Relevance
“…Similarly, a previous study reported that women with less than a high school degree have the highest prevalence of smoking during pregnancy, followed by those with a high school diploma or GED [7]. Prior findings also indicate that women with the lowest levels of education are most likely to smoke before pregnancy and continue smoking during pregnancy [15][16][17]. In our study, the prevalence increased significantly among women with less than a high school degree, despite decreasing in all other groups.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a previous study reported that women with less than a high school degree have the highest prevalence of smoking during pregnancy, followed by those with a high school diploma or GED [7]. Prior findings also indicate that women with the lowest levels of education are most likely to smoke before pregnancy and continue smoking during pregnancy [15][16][17]. In our study, the prevalence increased significantly among women with less than a high school degree, despite decreasing in all other groups.…”
Section: Discussionmentioning
confidence: 94%
“…49 Preterm birth and low birth weight have been consistently shown to be risk factors for neuropsychiatric disorders, [50][51][52][53][54] and in sibling comparisons. 51,52 Evidence from a meta-analysis and from large population-based studies suggests that depressed mothers are more likely to smoke throughout pregnancy, 41,55 and prenatal smoking has been repeatedly associated with the risk of neuropsychiatric disorders in the offspring. 21,56,57 Also in the PREDO, prenatal smoking was associated with increased internalizing, externalizing total psychiatric and ADHD problems in children.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen papers (Table 5) were included on predictors of smoking or barriers to cessation for women [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. Barriers and predictors of smoking cessation during pregnancy can be broadly divided into factors operating at the health provider (HP) level, social level and individual level.…”
Section: Predictors Of Smoking and Barriers To Cessationmentioning
confidence: 99%